Modelling the influence of microstructural morphology and triple junctions on hydrogen transport in nanopolycrystalline nickel. (15th June 2015) - Jothi, Sathiskumar; Croft, T.N.; Brown, S.G.R.
Abstract: Hydrogen transport in nanopolycrystalline (NPC) face centred cubic (FCC) nickel has received considerable attention as a result of the material's unique structural embrittlement behaviour. Triple junctions, where three grain boundaries meet, play an important role in hydrogen diffusion. Experiments have indicated that hydrogen transport at a triple junction (TJ) is orders of magnitude greater. In this contribution, a multiphase NPC model is proposed and used to investigate the influence on hydrogen transport of TJs within the surface of the NPC nickel using finite nanostructural element analyses. This 2D multiphase NPC model increases the density of triple junctions as the grain size reduces. The multiphase NPC model consists of two phases comprising nano grain interiors (GI) and intergranular phases. The intergranular (Ig) phase is divided into grain boundary affected zones (GBAZ) regions and TJ regions. The results of this finite nanostructural analysis show that hydrogen transport is enhanced at TJs and the bulk diffusion of hydrogen in NPC material is faster as the volume fraction of TJ increases and nano grain size decreases. The accumulation of hydrogen in three phase (GI, GBAZ, and TJ) microstructures is higher than the two phase (GI and Ig) microstructure case. The accumulation of hydrogen in TJ and Ig are heterogeneous in NPC nickel. The importance of the microstructural morphology in terms of the presence of pores, fine grains in TJ, changes in the shape of TJ with changes in the density of TJ and a TJ effect related to hydrogen transport in NPC nickel is all evidenced. This means that the TJ and microstructural morphology cannot be neglected when predicting hydrogen transport in a NPC nickel.